Body as “Leased out” Land: Land-Women Embodiment in Devi’s and Huq’s Selected Stories - Maknun Akter; Shirin Akter Popy (Asiatic: IIUM Journal of English Language and Literature, 2025)
This article undertakes a postcolonial ecofeminist critique of Mahasweta Devi’s “Douloti the Bountiful” and Hasan Azizul Huq’s “The Daughter and the Oleander,” set against the backdrop of brutal tribal realities and post-partition migration in India, respectively. Postcolonial ecofeminism, positioned at the intersection of postcolonial and ecological discourse, highlights the shared subjugation of women and nature in the Global South. While rooted in Western ecofeminist concerns regarding the feminisation of nature and the naturalisation of women, it deconstructs the mind-body dualism and examines the women-nature connection through the material realities of ethnic, cultural, colonial, racial, and gendered hegemony. Postcolonial ecofeminism, particularly in postcolonial landscapes, critiques Western ecofeminists’ symbolic association between women and land, arguing that such connections must be reevaluated in the contexts where sexual violence and economic exploitation define women’s lived experiences. A critical reading of “Douloti the Bountiful” and “The Daughter and the Oleander” reveals that, within impoverished economies, women’s youthful and beautiful bodies are commodified as financial resources, often through forced prostitution. Drawing on Neelam Jabeen’s assertions, this study contends that in both narratives, the female body functions as an exploited site—analogous to fertile land that is continuously cultivated for crops and cash crops—underscoring the fact that in the Global South, the land-woman embodiment is not merely symbolic but a lived and material reality.